(untitled) (Journal of Bangladesh Academy of Sciences, 2018)
Solar cell is a device that converts photons into electricity. The performance of a solar cell depends on its efficiency. The efficiency of a solar cell depends on some atmospheric variables such as light intensity, temperature, pressure, wind, humidity, precipitation and the sky condition etc. Geographical locations are the main factor for the variation of atmospheric variables. Due to atmospheric variables the solar cell efficiency is not same for all places of the World. Solar cell has been analyzed from different approach to improve its efficiency. The objective of this research is to analyze the efficiency of a silicon solar panel at three different places: Chittagong University Campus, Sandwip Island and Shibpur thana of Narshingdi district of Bangladesh. The efficiency mostly depends on the light intensity and temperature, however slightly depends on humidity. The experimental study shows that among the three places Norshingdi district is more suitable for solar power with the efficiency of 16.25% than other two places, where the efficiencies are 15.7% at Chittagong University Campus and 15.83% at Sandwip Island. Journal of Bangladesh Academy of Sciences, Vol. 42, No. 1, 99-104, 2018